PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB GOOGLE SITES PADA MATERI KEBERAGAMAN BUDAYA KEBERAGAMAN BUDAYA KELAS V SD NEGERI KETAMI II - Dwi Lingga Astuti; Frans Aditia Wiguna; Nara Setya Wiratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low understanding of fifth-grade students at SD Negeri Ketami II Kediri City regarding cultural diversity material due to learning activities that were still dominated by lecture methods and textbooks. The purpose of this study was to determine the validity, practicality, and effectiveness of an interactive learning media based on Google Sites. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 28 fifth-grade students. Data were collected through observation, interviews, questionnaires, and tests. The results showed that the media achieved a very high level of validity, with media expert validation reaching 96% and material expert validation reaching 94%. The practicality level was indicated by teacher responses of 96% and student responses of 97.5%. The media was also found to be highly effective, with a post-test learning mastery percentage of 94.2%. Therefore, the interactive learning media based on Google Sites is feasible to support cultural diversity learning in elementary schools.